Sexual knowledge, risk behavior, and access to reproductive health services among orphaned adolescents in Southwest Nigeria: implications for institutionalized care - Faramade, Ifedola Olabisi; Olugbenga-Bello, Adenike Iyanuoluwa; Goodman, Olayinka Olufisayo (Frontiers in Global Women's Health, 2023)
Introduction: An orphan has been defined as a child under eighteen years of age who has lost one or both parents to any cause. It has been reported that for every ten Nigeria children, one is likely to be an orphan. Adolescents are faced with a serious challenge meeting their reproductive health need which often times becomes overwhelming especially when orphaned. Objectives: We compared institutionalized and non-institutionalized orphaned adolescents for their knowledge of sexuality, risky sexual practice and access to reproductive health services (RHS). Methods: The study adopted a cross-sectional descriptive study design conducted via structured, pre-tested, interviewer-administered questionnaires among 205 orphaned adolescents (140 institutionalized and 65 non-institutionalized). Data were analyzed using the Statistical Product and Service Solution (SPSS version 25.0) and summarized using frequency, mean and percentages, and inferential statistics. All analyses were done at a 95% confidence interval and p<0.05 level of Results: Majority of non-institutionalized respondents (73.8%) showed good knowledge compared with 56.4% of orphans in institutions (χ2=5.713, p=0.017). Institutionalized orphans showed higher practice of good sexual behavior (80.7%) compared with non-institutionalized respondents (64.6%) (χ2=6.239, p=0.011). Access to reproductive health services was slightly higher among institutionalized (66.4%) than non-institutionalized respondents (64.6%). Conclusion: Institutionalized and non-institutionalized orphans differ in their knowledge of sexuality, sexual behavior and risky practices including access to reproductive health services. The study demonstrated the effectiveness of institutionalized care of orphans towards improved access to reproductive health services and good sexual practice. The government and relevant stakeholders should advocate for better sexuality education and understanding, make sure that access barriers for orphans are removed, orphans utilize the facilities for reproductive health that are available, and make sure that adolescent health policies are implemented effectively. Key words: sexual knowledge, risk behavior, access, reproductive health services, orphaned adolescents, institutionalized-care, Nigeria